FABRIKASI DAN KARAKTERISASI ELEKTRODA KARBON DARI BIOMASSA SERABUT BUAH NIPAH DENGAN VARIASI KONSENTRASI AKTIVATOR KOH - Ade Nur Indah Lestari; Rakhmawati Farma; Vepy Asyana; Awitdrus Awitdrus (Universitas Riau, 2020)
Today the need for electrical energy has increased due to the large number of electronic devices that require high electrical energy. To overcome this, a large storage of electrical energy is needed. One of the constituents of energy storage devices that is very important is the electrode. This study used nipah fibers as the basic material for electrodes, because the potential of nipah fruit has not been widely used. The purpose of this study was to determine the effect of KOH activator on the quality of activated carbon from nipah fruit fibers using variations of KOH activator concentrations 0.2 M, 0.3 M, and 0.4 M with sample codes SBN-02, SBN-03, and SBN-04. The manufacture of activated carbon electrodes is carried out through a process of pre-carbonization, chemical activation, carbonization, and physical activation. Characterization of TGA resulted in a resistant temperature of 296°C with a maximum speed of 0.166mg/min. XRD analysis produced a semicrystalline diffraction pattern consisting of two peaks around 24° and 44° at an angle of 2θ indicating the orientation of the hkl (002) and (001) planes.